2005
DOI: 10.1111/j.1467-7679.2005.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

When Popular Participation Won't Improve Service Provision: Primary Health Care in Uganda

Abstract: Advocates of participatory approaches to service delivery see devolution as key to empowering people to take charge of their own affairs. Participation is portrayed as guaranteeing the delivery of services that are in line with user preferences. It is assumed that people are keen to participate in public affairs, that they possess the capacity to do so, and that all they need is opportunities. Using evidence from ethnographic research in Uganda, this article questions these views. It shows that, to succeed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 29 publications
7
36
0
Order By: Relevance
“…This finding is supported by Golooba-Mutebi’s discussion of similar experiences with the implementation of health unit management committees (HUMC) in Mukono District, Uganda [53]. Golooba-Mutebi found that HUMC were successful at a time when AMREF, implementing a World Bank project, paid allowances to members of HUMC to attend meetings and write reports but HUMC nearly grounded to a halt as they transitioned to the government formal structures [53]. While linking social capital espouses partnerships as an essential ingredient in the processes that involve connecting people to formal social services [33], this finding suggests that potential partnerships for effective linkages can be seriously hampered if other interested stakeholders become central players at a later stage in an intervention.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This finding is supported by Golooba-Mutebi’s discussion of similar experiences with the implementation of health unit management committees (HUMC) in Mukono District, Uganda [53]. Golooba-Mutebi found that HUMC were successful at a time when AMREF, implementing a World Bank project, paid allowances to members of HUMC to attend meetings and write reports but HUMC nearly grounded to a halt as they transitioned to the government formal structures [53]. While linking social capital espouses partnerships as an essential ingredient in the processes that involve connecting people to formal social services [33], this finding suggests that potential partnerships for effective linkages can be seriously hampered if other interested stakeholders become central players at a later stage in an intervention.…”
Section: Discussionmentioning
confidence: 64%
“…However, from AMREF to government structures, there was a transition failure , which culminated in “accusations” from community members and VHTs of government neglect, failure to equip the VHTs and sustain an incentive structure initiated by AMREF, which affected the linkages. This finding is supported by Golooba-Mutebi’s discussion of similar experiences with the implementation of health unit management committees (HUMC) in Mukono District, Uganda [53]. Golooba-Mutebi found that HUMC were successful at a time when AMREF, implementing a World Bank project, paid allowances to members of HUMC to attend meetings and write reports but HUMC nearly grounded to a halt as they transitioned to the government formal structures [53].…”
Section: Discussionmentioning
confidence: 87%
“…While an absence of choice, and therefore an inability to exit, may on the one hand make the exercise of voice more pressing (Golooba-Mutebi, 2005) it may simultaneously undermine it.…”
Section: (Ii) Monopoly Tendencymentioning
confidence: 97%
“…Escobar 2001; Escobar et al . 2002) and a range of empowerment‐oriented participatory approaches to development (see Mohan and Stokke 2000; Cooke and Kothari 2001; Simon et al 2003; Golooba‐Mutebi 2005). By contrast, the universalizing neoliberal‐inspired approaches imply or advocate global cultural convergence/homogenization through the assimilation of western capitalist consumer culture, and are thus very much metanarratives constituting latter‐day versions of modernization theory (Nederveen Pieterse 2004, 7–21).…”
Section: The ‘Cultural Turn’ and Postcolonialismmentioning
confidence: 99%